2008
DOI: 10.1007/s11101-008-9104-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated effects in the Brassicaceae on the performance and behaviour of parasitoids

Abstract: Direct and indirect plant defences are well studied, particularly in the Brassicaceae. Glucosinolates (GS) are secondary plant compounds characteristic in this plant family. They play an important role in defence against herbivores and pathogens. Insect herbivores that are specialists on brassicaceous plant species have evolved adaptations to excrete or detoxify GS. Other insect herbivores may even sequester GS and employ them as defence against their own antagonists, such as predators. Moreover, high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 133 publications
(149 reference statements)
1
132
1
Order By: Relevance
“…These chemical cues are important signals for orientation of both carnivorous enemies and herbivores, including distant host location by arthropods (Karban and Baldwin, 1997;Dicke, 1999;Dicke and Van Loon, 2000;Arab and Bento, 2006). Plants' responses upon damage caused by herbivores occurs through the regulation of several biochemical pathways that lead to the release of chemical compounds, which cause either repellence to herbivore insects or attraction to natural enemies (predators or parasitoids) of herbivore insects (Karban and Baldwin, 1997;Dicke and Van Loon, 2000;Pickett et al, 2003;Arab and Bento, 2006;Gols and Harvey, 2009). Attracted by herbivory-induced plant volatiles, parasitoids of herbivores perform host searching to lay their eggs in or on them as shown in recent studies (Mattiacci et al, 1994;Takabayashi and Dicke, 1996;Dicke, 1999;Hilker and Meiners, 2002;Fatouros et al, 2005b;Heil, 2008).…”
Section: "Nearly 75% Of the World's Macroscopic Biodiversity Is Tied mentioning
confidence: 99%
“…These chemical cues are important signals for orientation of both carnivorous enemies and herbivores, including distant host location by arthropods (Karban and Baldwin, 1997;Dicke, 1999;Dicke and Van Loon, 2000;Arab and Bento, 2006). Plants' responses upon damage caused by herbivores occurs through the regulation of several biochemical pathways that lead to the release of chemical compounds, which cause either repellence to herbivore insects or attraction to natural enemies (predators or parasitoids) of herbivore insects (Karban and Baldwin, 1997;Dicke and Van Loon, 2000;Pickett et al, 2003;Arab and Bento, 2006;Gols and Harvey, 2009). Attracted by herbivory-induced plant volatiles, parasitoids of herbivores perform host searching to lay their eggs in or on them as shown in recent studies (Mattiacci et al, 1994;Takabayashi and Dicke, 1996;Dicke, 1999;Hilker and Meiners, 2002;Fatouros et al, 2005b;Heil, 2008).…”
Section: "Nearly 75% Of the World's Macroscopic Biodiversity Is Tied mentioning
confidence: 99%
“…For Brassicaceae species it was found that volatile emissions are very similar when plant are damaged by different herbivores and parasitoids cannot detect these differences (Gols & Harvey, 2009). For example our results show that S. aff.…”
Section: Discussionmentioning
confidence: 63%
“…For example, plant glucosinolates occurring within herbivore prey negatively affect a wide range of parasitoids (Gols and Harvey, 2009). While we focus here on root microbial mutualists, we note that there is now abundant evidence of root-feeding herbivores influencing the chemistry of plant tissues above ground, with subsequent effects on herbivore and enemy performance (Hunter, 2016).…”
Section: Prey Qualitymentioning
confidence: 99%